Comparative proteomics of cucurbit phloem indicates both unique and shared sets of proteins - Lopez-Cobollo,RM; Filippis,I; Bennett,MH; Turnbull,CG (The Plant Journal, 2016)
Cucurbits are well studied phloem biology models but unusually possess both fascicular phloem (FP) within vascular bundles and additional extrafascicular phloem (EFP). Although the functional differences between the two systems are not yet clear, sugar analysis and limited protein profiling previously established that FP and EFP have divergent composition. Here we report a detailed comparative proteomics study of FP and EFP in two cucurbits, pumpkin and cucumber. We re-examined the sites of exudation by video microscopy, and confirmed that in both species, the spontaneous exudate following tissue cutting derives almost exclusively from EFP. Comparative gel electrophoresis and mass spectrometry-based proteomics of exudates, sieve element contents and microdissected stem tissues established that EFP and FP profiles are highly dissimilar, and that there are also species differences. Searches against cucurbit databases enabled identification of more than 300 FP proteins from each species. Few of the detected proteins (~10%) were shared between sieve element contents of FP and EFP, and enriched Gene Ontology categories also differed. To explore quantitative differences in the proteomes, we developed multiple reaction monitoring methods for cucumber proteins that are representative markers for FP or EFP and assessed exudate composition at different times after tissue cutting. Based on failure to detect FP markers in exudate samples, we conclude that FP is blocked very rapidly and therefore contributes minimally to the exudates. Overall, the highly divergent contents of FP and EFP indicate that they are substantially independent vascular compartments. This article is protected by copyright. All rights reserved.